Applying CIPP model to evaluate aftercare services for drug addicts in Saudi Arabia - Hajari Ahmed, Alayshi; Fauziah Ibrahim, Aizan Sofia Amin, Mohammad Rahim, (Opción, 2019)
Recent problems to confront the problem of drug addiction have urged the researcher to evaluate the aftercare services. To achieve a better evaluation, this study seeks to fulfill the first objective of examining the nature of relationship between “Context, Input, and Process”with“Product” as the main parts of the aftercare program’s services. Also, it aims discover which one of context, input and process is regarded to be more effective on the product in achieving the. Applying mentioned methods of study, the obtained results showed a decline in the number of individual back to drugs after curing